2022
DOI: 10.3390/ijms23073785
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metabolic Alterations in Alzheimer’s Disease

Abstract: The brain is one of the most energy-consuming organs in the body. Satisfying such energy demand requires compartmentalized, cell-specific metabolic processes, known to be complementary and intimately coupled. Thus, the brain relies on thoroughly orchestrated energy-obtaining agents, processes and molecular features, such as the neurovascular unit, the astrocyte–neuron metabolic coupling, and the cellular distribution of energy substrate transporters. Importantly, early features of the aging process are determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 315 publications
0
21
0
Order By: Relevance
“…Metabolic alterations are an important feature within the AD pathology [ 10 , 75 ], particularly the brain insulin resistance that has been closely tied to cognitive deficiencies [ 4 , 13 , 76 ]. Extensive literature points towards a link between T2DM, obesity, insulin resistance, and an elevated risk of developing AD and related disorders [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic alterations are an important feature within the AD pathology [ 10 , 75 ], particularly the brain insulin resistance that has been closely tied to cognitive deficiencies [ 4 , 13 , 76 ]. Extensive literature points towards a link between T2DM, obesity, insulin resistance, and an elevated risk of developing AD and related disorders [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oscillations in this band activate microglia and clear amyloid-β deposits, and this effect is only present at 40 Hz, not at other frequencies ( Iaccarino et al, 2016 ; Dhaynaut et al, 2022 ; Liu C. et al, 2022 ; Shen et al, 2022 ). Features of neurodegenerative diseases include abnormal protein aggregation, impaired protein degradation, failure of axonal transport, mitochondrial dysfunction, reduced energy metabolism, oxidative damage, and cell death ( Mattson et al, 1999 ; Ardanaz et al, 2022 ). 40 Hz-tACS can address the AD pathophysiological cascade by modulating interneuronal activity that leads to global network dysfunction and activating microglia waste removal ( Matsumoto and Ugawa, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…(2) Considerable or even complete loss of NeuN immunoreactivity was also reported for neurons affected by ischemic insults (middle cerebral artery occlusion) without significant cell loss [25] or in neurons that just entered the cell death process [26]. Interestingly, these neuronal populations are of special interest because energy and nutritional deficiency and cell loss are essential characteristics of the AD brain [27]. (3) The intensity of NeuN staining is reported to be lower in AD samples [28], and further (4) due to many NeuN negative cortical neurons in FTLD-TDP (frontotemporal lobar degeneration with TDP-43 inclusions) patients, Yousef et al suggested NeuN staining as an indicator of healthy neurons [29].…”
Section: Introductionmentioning
confidence: 99%